The association between gait speed and falls in ambulatory adults with spinal muscular atrophy: a retrospective pilot study - Jira, Kathryn; Jaworek, Andrea; Allen, Matti; Zhao, Songzhu; Kelly, Kristina; Arnold, W. David; Elsheikh, Bakri (Frontiers in Neurology, 2024)
IntroductionFatigue and gait speed are established determinants of fall risk in patients with neurological disorders. However, data on adults with spinal muscular atrophy (SMA) is limited. The aim of this pilot study was to investigate falls and risk factors in adults with SMA.MethodsA retrospective chart review of ambulatory adults with genetically confirmed 5q-SMA included: age, sex, age of symptom onset, SMN2 copy number, BMI, and 6MWT distance and speed at minutes 1, 2, and 6.ResultsFourteen ambulatory patients were included in the analysis with an average follow-up of 36 months (range of 12–66 months). 10 patients were classified as fallers (Fall) and four as non-fallers (NFall). One faller received Risdiplam, while the remaining fallers and non-fallers received Nusinersen for the duration of the follow-up period. In the Fall cohort, the median speed at 1, 2, and 6 min were 0.92 m/s, 0.89 m/s, and 0.77 m/s, respectively, with a heterogeneous range including one faller at 1.25 m/s. In the NFall cohort, the slowest collected median recorded speeds were 1.18 m/s, 1.11 m/s, and 1.09 m/s respectively, with one non-faller at 0.56 m/s. There was no significant statistical difference between 6-min gait speeds and individuals experiencing falls. However, we found a three-fold greater decline in speed between the 6MWT first and last minute in the Fall (13.01%) compared to the NFall (5.16%). 7 of 10 patients had multiple falls (70%) with two individuals consequently losing ambulation (20%).DiscussionThese findings underscore the need for larger studies on fatigability and the importance of considering factors beyond gait speed alone.